Clinical impact of post‐induction resolution of pulmonary lesions in metastatic Ewing sarcoma. Issue 4 (15th January 2020) - Halalsheh, Hadeel; Kaste, Sue C.; Krasin, Matthew J.; Sykes, April; Sahr, Natasha; Spunt, Sheri L.; Federico, Sara M.; Bishop, Michael W.
Abstract: Background: Patients with metastatic Ewing sarcoma experience poor outcomes despite intensive systemic and local therapy. Early chemotherapy response of pulmonary metastases has been associated with prognosis in other pediatric malignancies. We reviewed the outcomes of patients with Ewing sarcoma and pulmonary metastases treated at our institution based on therapy received and early pulmonary response. Materials and methods: We retrospectively reviewed patients with newly diagnosed Ewing sarcoma and pulmonary metastases at St. Jude Children's Research Hospital between 1979 and 2015. Data obtained included demographic and treatment characteristics including chemotherapy, local control measures, whole lung irradiation (WLI) administration, autologous stem cell transplantation, and outcomes. Patients were evaluated for radiographic post‐induction pulmonary complete response (CR). We estimated event‐free survival (EFS) and overall survival (OS) and used Cox proportional hazards regression to examine the effects of clinical and treatment factors on outcomes. Results: Fifty‐four patients (median age, 12.9 years) were evaluated. Post‐induction pulmonary CR was observed in 33 (61%) patients. WLI was delivered to 16 patients (4/33 with pulmonary CR and 12/21 with non‐CR). At median 3.6 years follow‐up, five‐year EFS and OS were 30.8% ± 6.4% and 49.6% ± 7.1%, respectively. Post‐induction pulmonary CR was associated with prolonged EFS ( P  < 0.001) but not improved OS ( P  = 0.065). Post‐induction pulmonary CR was associated with a lower incidence of lung failure ( P  = 0.031). Conclusions: Post‐induction pulmonary CR is associated with improved EFS in patients with Ewing sarcoma who present with pulmonary metastases.